2005
DOI: 10.5858/2005-129-1032-dphfsc
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Pseudoepitheliomatous Hyperplasia From Squamous Cell Carcinoma in Mucosal Biopsy Specimens From the Head and Neck

Abstract: Context.—The differentiation of pseudoepitheliomatous hyperplasia from invasive squamous cell carcinoma is a difficult and frequently encountered distinction, especially in biopsy specimens from head and neck mucosa. The problem is compounded by inflamed and often poorly oriented tissue sections. Objective.—To distinguish pseudoepitheliomatous hyperplasia from invasive squamous cell carcinoma, utilizing a panel of antibodies to various epithelial and stromal elements (p53, matrix metalloproteina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Black on 16 cases of OSCC revealed its decreased staining in the invasive cells 12. Likewise a study by Sridevi et al showed that 60% subjects showed weak, 30% mild to moderate and remaining 10% moderate to strong expression and also revealed loss of E-cadherin expression in tumour which is in agreement to our findings.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Black on 16 cases of OSCC revealed its decreased staining in the invasive cells 12. Likewise a study by Sridevi et al showed that 60% subjects showed weak, 30% mild to moderate and remaining 10% moderate to strong expression and also revealed loss of E-cadherin expression in tumour which is in agreement to our findings.…”
supporting
confidence: 92%
“…11 Loss of E-Cadherin fragment causes breakage of adherent junctions which results in detachment of epithelial cells making them vulnerable for invading the deeper tissues in oral cancers. 12 E-cadherin has frequently been studied as a potential cancer biomarker and is hypothesized that its expression might be useful in differentiating OSCC from PEH. 10 This is essential as erroneous diagnosis of malignancy results in radical surgery, treatment related morbidity and can even have fatal consequences.…”
mentioning
confidence: 99%
“…[4] It is often difficult to distinguish PEH from SCC. The SCC shows increased staining for p53 and MMP-1 and less intense staining for E-cadherin [5] plus, the universal cytological criteria for SCC are nuclear enlargement, hyperchromasia, irregular nuclear outline, coarse nuclear chromatin, and prominent nucleoli. [6] The presence of a nodular lesion with feeder vessels and intrinsic vascularity should raise a suspicion of invasive SCC [7] as was seen in our case, and hence, the word "diagnostic dilemma" is one of the most appropriate words for this lesion.…”
Section: Discussionmentioning
confidence: 96%
“…Two of these features, i.e., Atypical mitoses and dyskeratosis, are of value even on small biopsies (21)(22)(23). Nonetheless, exceptional difficulty may be encountered in differentiating the above two in small biopsies, and immunohistochemistry for p53, Matrix metalloproteinase 1, and E-cadherin have been found to be useful (24). In one of the case series from the same institute (2007), five cases of histoplasmosis were reported, which had clinically presented as carcinoma involving the oral cavity (3 cases), hypopharynx (1case), and larynx (1 case).…”
Section: Discussionmentioning
confidence: 99%